Targeted delivery of anti-miR-155 by functionalized mesoporous silica nanoparticles for colorectal cancer therapy - Li Y (Dove Medical Press, 2018)
Yang Li,1,2,* Yanhong Duo,1,3,* Jiangang Bi,1 Xiaowei Zeng,4 Lin Mei,4 Shiyun Bao,1 Lisheng He,5 Aijun Shan,2 Yue Zhang,1 Xiaofang Yu1 1Department of Hepatobiliary and Pancreas Surgery, Second Clinical Medical College of Jinan University, Shenzhen People’s Hospital, Shenzhen 518020, China; 2Department of Emergency, Second Clinical Medical College of Jinan University, Shenzhen People’s Hospital, Shenzhen 518020, China; 3Key Laboratory of Plant Cell Activities and Stress Adaptation, Ministry of Education, School of Life Sciences, Lanzhou University, Lanzhou 730000, China; 4Division of Life and Health Sciences, Graduate School at Shenzhen, Tsinghua University, Shenzhen 518020, China; 5Department of Pathology, Second Clinical Medical College of Jinan University, Shenzhen People’s Hospital, Shenzhen 518020, China *These authors contributed equally to this work Introduction: MicroRNA-155 (miR-155) is an oncogenic microRNA, which is upregulated in many human cancers including colorectal cancer (CRC). Overexpression of miR-155 has been found to regulate several cancer-related pathways, and therefore, targeting miR-155 may be an effective strategy for cancer therapy. However, effective and safe delivery of anti-miR-155 to tumors remains challenging for the clinical applications of anti-miR-155-based therapeutics.Methods: In this study, we explored the expression of miR-155 and the transcription factor nuclear factor kappa B (NF-κB) in CRC tissues and cell lines, and the possible relationship between miR-155 and NF-κB. We further report on anti-miR-155-loaded mesoporous silica nanoparticles (MSNs) modified with polymerized dopamine (PDA) and AS1411 aptamer (MSNs-anti-miR-155@PDA-Apt) for the targeted treatment of CRC.Results: Results showed that miR-155 is overexpressed in CRC tissues and cell lines, and there is a positive feedback loop between NF-κB and miR-155. Compared to the control groups, MSNs-anti-miR-155@PDA-Apt could efﬁciently downregulate miR-155 expression in SW480 cells and achieve significantly high targeting efficiency and enhanced therapeutic effects in both in vivo and in vitro experiments. Furthermore, inhibition of miR-155 by MSNs-anti-miR-155@PDA-Apt can enhance the sensitivity of SW480 to 5-fluorouracil chemotherapy.Conclusion: Thus, our results suggested that MSNs-anti-miR-155@PDA-Apt is a promising nanoformulation for CRC treatment. Keywords: miR-155, mesoporous silica nanoparticles, AS1411 aptamer, NF-κB, 5-fluorouracil